DORIS LESSINGNING “PARVOZ” (“FLIGHT”) HIKOYASIDA AVLODLAR ZIDDIYATI VA AYOL SUBYEKTIVLIGINING RAMZIY IFODASI - Davlatova Vazira (PEDAGOGS, 2025)
This article presents an analysis of the short story Flight by the English writer Doris Lessing through feminist and psychological approaches. At the heart of the narrative lies the emotional struggle of an elderly grandfather who cannot come to terms with his granddaughter Alice’s decision to begin an independent life and marry the man she loves. The story explores the emotional tensions, misunderstandings, and psychological processes among three generations—grandfather, daughter (Alice’s mother Lucy), and granddaughter—through the use of artistic symbolism. The central conflicts of the story are rooted in generational differences and the young woman’s assertion of her subjectivity (personal choice, freedom, and independence). The grandfather’s actions of caging and releasing pigeons are directly tied to Alice’s pursuit of autonomy and are rich in symbolic and psychological meaning. The pigeon, in particular, serves as a metaphor for female freedom and the right to self-determination. The feminist analysis highlights the development of female characters, their search for voice, and resistance to patriarchal control. From a psychological perspective, the short story reflects the grandfather’s fear of loss, emotional instability associated with aging, and the emotional disconnection between generations. Doris Lessing conveys these themes through emotional intensity, delicate symbolism, and a quiet yet deeply dramatic narrative structure. Ultimately, through Flight, the author offers a sincere and poetic depiction of familial relationships, shifting values in modern society, and the struggle of a woman to shape her subjectivity. This analysis helps to understand the story not only as a literary work but also as a socio-psychological phenomenon.